Factors influencing consumers’ willingness to purchase genetically modified organism (GMO) food products in Klang Valley, Malaysia - Uddin, Mohi; Islam, Mohd Aminul; Hossin, M.M Ismail (Scholars Middle East Publishers, 2018)
The results of the survey showed that consumers generally know (53.3%) what genetically modified organisms (GMOs) are, but they do not have enough information about the genetic modification process. The main concerns of consumers about GMO foods are their carcinogenic effects to human. The usage of GMOs in health sector and in preventing environmental pollution were the most approved areas by the consumers, whereas the majority of consumers disapproved the use of genetic modifications in food applications. This study shows that knowledge, perceived risks, attitude, labeling have a significant relationship with willingness to purchase GMO food products based on the survey conducted in Klang Valley, Malaysia. The study showed importance of willingness to purchase GMO food products to determine the success of the business with human needs. So, this study will help the GMO food products entrepreneur to plan and run their business accordingly to achieve success. In addition to that, the survey data will be helpful to the GMO authority, to understand the behavior intention of the consumers of Malaysia, which will help them for further research as well as to take adequate measures for the better managerial implications of the GMO food products company in Malaysia.